2013
DOI: 10.1016/j.jviromet.2013.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Combination of allele-specific detection techniques to quantify minority resistance variants in hepatitis B infection: A novel approach

Abstract: Detection of minor variant viral quasispecies of the rtV173L+rtL180M+rtM204V combination mutation in the hepatitis B virus (HBV) polymerase mediating both lamivudine resistance and vaccine escape is potentially important for tracking the development and evolution of resistance within both individuals and populations. A highly sensitive and specific assay to quantitate HBV genomes was developed with this mutation combination directly from viral DNA in serum using allele-specific quantitative PCR with locked nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…We suggest using a sample-specific reference sequence as a mapping reference for NGS analysis in studies of P-gene variants for drug-resistance [ 24 , 25 ] and S-gene variants for the pathogenesis of HCC [ 26 , 27 ]. Emerging evidence supports the notion that certain drug-resistant HBV minor strains are crucial for the progression of liver diseases and are predictors of subsequent treatment failure [ 23 , 28 ]. They may accumulate and eventually dominate under a long-term selection effect during antiviral treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…We suggest using a sample-specific reference sequence as a mapping reference for NGS analysis in studies of P-gene variants for drug-resistance [ 24 , 25 ] and S-gene variants for the pathogenesis of HCC [ 26 , 27 ]. Emerging evidence supports the notion that certain drug-resistant HBV minor strains are crucial for the progression of liver diseases and are predictors of subsequent treatment failure [ 23 , 28 ]. They may accumulate and eventually dominate under a long-term selection effect during antiviral treatment [ 23 ].…”
Section: Discussionmentioning
confidence: 96%
“…Bhattacharya D et al successfully developed an allele-specific quantitative PCR with combination of locked nucleic acid primers and a minor groove binder probe for the quantitative determination of minor viral quasispecies of the triple combination mutation rtV173L+rtL180M+rtM204V within one HBV genome. The assay could accurately detected 3×10 2 copies of the triple mutant in the 3×10 8 copies background of wild-type DNA [16] .…”
Section: Discussionmentioning
confidence: 99%
“…And there was not a specific guideline on choosing the last position versus the penultimate position for incorporation of the LNA base so far. To a great extent, the position of LNA was determined empirically [16] . Most studies had shown a 3′ LNA residue in the primer at the SNP site (i.e., the mismatch site) could improve mismatch discrimination excellently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation